PENGARUH VARIASI WAKTU PERENDAMAN SAMPEL DAN JUMLAH PELARUT HOMOGENASI TERHADAP PERSENTASE EKTRAK PROTEIN DAUN KELOR (Moringa oleifera) - Meirita Sari; Methatias Ayu Moulina (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2020)
This research is one form of utilization of food plants, namely Moringa (Moringa oleifera). M. oleifera can grow well in Bengkulu Province. The leaves of M. oleifera contain protein compounds that behave like lectins. This compound can be used as an antimicrobial material. The stages in this study include the extraction of M. oleifera leaf protein using salting in and salting out methods. This study aims to determine the effect of the immersion time and the amount of solvent in the homogenation stage extraction process on the percentage of protein extract. The results showed that the immersion time had a significant effect compared to the amount of solvent in the homogenation stage of Moringa oleifera leaf protein extraction. The longer the time needed, the greater the percentage of M. oleifera leaf protein extract. This research is useful for researchers, the public, the health sector, and the development of science and education. Keywords: Moringa oleifera, Extraction, Protein